Efficiency of the CL, DRIS and CND Methods in Assessing the Nutritional Status of Eucalyptus spp. Rooted Cuttings - Barros de Morais, Thais Chagas [UNESP]; Prado, Renato de Mello [UNESP]; Franklin Traspadini, Edilaine Istefani [UNESP]; Salvador Wadt, Paulo Guilherme; Paula, Rinaldo Cesar de [UNESP]; Souza Rocha, Antonio Marcio [UNESP] (Mdpi, 2019)
The efficiency of methods in adequately interpreting the nutritional status of Eucalyptus spp. rooted cuttings remains unknown. The aim was to evaluate the quality of diagnoses obtained using the critical level (CL), diagnosis and recommendation integrated system (DRIS) and compositional nutrient diagnosis (CND) methods to assess the nutritional status of Eucalyptus spp. rooted cuttings, based on two different yield indicators. The data were obtained from commercial nursery and calibration experiments, using seven nutrients as treatments (N, P, K, Mg, Ca, B and Fe) and four concentrations per nutrient, arranged in randomized blocks, with four repetitions. The Eucalyptus spp. clone used in the experiments was AEC 0144. A total of 222 rooted cuttings were obtained from the experimental area and commercial nurseries and the following were determined: leaf nutrient content, whole plant dry matter (DM) content and the Dickson quality index (DQI). Diagnostic accuracy in the experimental plots was ascertained by comparing the diagnosis with plant response as a function of adding the corresponding nutrient. Five measures of accuracy were used to test the efficiency of the diagnostic methods: total accuracy, accuracy for deficiency and sufficiency, deficiency ratio, efficiency ratio, and the net increase in in DM and DQI. The performance of diagnostic methods varied between CL, DRIS and CND, and among the nutrients studied. Given that the seedling production system is largely more controlled, where environmental variations are minimal, and considering that the different diagnostic methods exhibited distinct performance in terms of assessing the true nutritional status of eucalyptus rooted cuttings, the CL method is the most indicated for this situation, due to its better performance in evaluating the nutritional status of most nutrients and easy implementation.
Keywords: forest species; rooted cuttings; increased yield; leaf diagnosis; nutritional diagnoses